Parenteral NSAIDs for acute treatment of migraine: Adherence to the IHS guidelines for controlled trials - John G Curran; John Waters; Hsiangkuo Yuan (SAGE Publishing, 2022)
Background: Parenteral non-steroidal anti-inflammatory drugs (NSAIDs) are important alternatives to oral NSAIDs, especially in patients with severe migraine who have emesis or gastroparesis. With increasing research on using parenteral NSAIDs for acute migraine, it is critical to examine the quality of these studies. Our goal was to assess the adherence of these trials to the International Headache Society (IHS) controlled trial guidelines for acute treatment of migraine. Methods: We queried PubMed for clinical trials investigating parenteral NSAIDs for acute treatment of migraine in adult patients. We developed a 14-point scoring system based on the essential components of the IHS guidelines. To date, four versions of the IHS's Guidelines for controlled trials of acute treatment of migraine attacks have been published. Each trial was evaluated with the appropriate edition of the guidelines. Results: We identified 216 studies and assessed 27 eligible clinical trials. The mean score was 6.7 ± 2.1 (2-11). Most trials followed the IHS migraine diagnosis criteria (85.2%), but only six (22.2%) selected patients based on the recommended headache frequency. Most trials were randomized (88.8%), but fewer were double-blinded (74.1%) or placebo-controlled (11.1%). Almost every trial clearly explained the pain scale (96.3%), and three-quarters (77.8%) assessed headache-associated symptoms. However, no trial utilized the recommended primary endpoint: pain-freedom at 2-hours. Conclusions: Most clinical trials on parenteral NSAIDs for acute migraine did not fully adhere to the IHS recommendations. Future studies should pay special attention to the IHS guideline to improve the quality of clinical trials for the acute treatment of migraine.